Agonist-Promoted Phosphorylation and Internalization of the Kappa Opioid Receptor in Mouse Brains: Lack of Connection With Conditioned Place Aversion - Chen, Chongguang; Huang, Peng; Bland, Kathryn; Li, Mengchu; Zhang, Yan; Liu-Chen, Lee-Yuan (Frontiers in Pharmacology, 2022)
Selective kappa opioid receptor (KOR) agonists are promising antipruritic agents and analgesics. However, clinical development of KOR agonists has been limited by side effects, including psychotomimetic effects, dysphoria and sedation, except for nalfurafine and recently CR845 (Difelikefalin). Activation of KOR elicits G protein- and -arrestin-mediated signaling. KOR-mediated analgesic and anti-pruritic effects are mediated by G protein signaling. However, different results have been reported as to whether conditioned place aversion (CPA) induced by KOR agonists is mediated by -arrestin signaling. In this study, we examined if there was a correlation between agonist-promoted CPA and KOR phosphorylation and internalization, proxies for -arrestin recruitment in vivo. We have reported that the KOR agonists U50,488H and methoxymethyl salvinorin B (MOM-SalB) cause CPA, whereas nalfurafine and 42B do not, at doses effective for analgesic and anti-scratch effects (1.8-2.8 x A50 of anti-scratch effect). In addition, U50,488H, MOM-SalB and 42b, but not nalfurafine, reduced novelty-induced hyperlocomotion. Moreover, U50,488H, MOM-SalB and 42b caused profound impairment in rotarod performance, but nalfurafine had only a slight change. Herein, we demonstrated that U50,488H, MOM-SalB and 42B, but not nalfurafine, promoted KOR phosphorylation at T363 and S369 in mouse brains, detected by immunoblotting with phospho-KOR specific antibodies. In addition, U50,488H, MOM-SalB and 42B, but not nalfurafine, caused KOR internalization in the ventral tegmental area of a mutant mouse line expressing a fusion protein of KOR conjugated at the C-terminus with tdTomato (KtdT). Taken together, these data reveal a lack of correlation between agonist-promoted KOR-mediated CPA with agonist-induced KOR phosphorylation and internalization. Rather, KOR phosphorylation and internalization appear to be correlated with hypolocomotion and impaired rotarod performance.